2001
DOI: 10.1074/jbc.m009720200
|View full text |Cite
|
Sign up to set email alerts
|

NCK and PAK Participate in the Signaling Pathway by Which Vascular Endothelial Growth Factor Stimulates the Assembly of Focal Adhesions

Abstract: Vascular endothelial growth factor (VEGF)-induced endothelial cell migration is a key step in the angiogenic response and is mediated, in part, by an accelerated rate of focal adhesion complex assembly and disassembly. We investigated the signaling pathway by which VEGF regulates focal adhesion complex assembly by examining the signaling proteins involved. VEGF stimulated the tyrosine phosphorylation of the SH2 domain-containing signaling proteins NCK and CRK in human umbilical vein endothelial cells. The sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 67 publications
1
57
1
Order By: Relevance
“…Recent reports have implicated Src and FAK in signal transduction linked to cell migration. [31][32][33][34] We thus prepared cell lysates from HUVEC stimulated with VEGF in the presence or absence of Sema-ECD. After SDS-PAGE, the resolved proteins were immunoblotted with a mAb to Src phosphorylated tyrosine 416 (pSrc-Y 416 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have implicated Src and FAK in signal transduction linked to cell migration. [31][32][33][34] We thus prepared cell lysates from HUVEC stimulated with VEGF in the presence or absence of Sema-ECD. After SDS-PAGE, the resolved proteins were immunoblotted with a mAb to Src phosphorylated tyrosine 416 (pSrc-Y 416 ).…”
Section: Resultsmentioning
confidence: 99%
“…Stoletov and colleagues have recently shown that VEGF stimulation recruited the Nck-Pak complex to focal adhesions, and the Nck-Pak complexed with FAK in human umbilical vein endothelial cells (HUVE). Introducing antisense oligonucleotides against Ncka into these cells inhibited VEGF-stimulated focal adhesion formation and migration (Stoletov et al, 2001). This ®nding suggests that Ncka has a speci®c role in VEGF signaling, since the 19-mer antisense oligonucleotide used by Stoletov et al (2001) unlikely cross reacted with Nckb mRNA and previous studies showed that both Ncka and Nckb are copresent in almost all cell types (Chen et al, , 2000, Nonetheless, it is important to test if down regulation of Nckb in these cells has any inhibitory e ects.…”
Section: Nck Links Cell Surface Receptors To the Actin Cytoskeletonmentioning
confidence: 99%
“…This suggests that Ncka and Nckb are functionally redundant during development. On the other hand, individual Nck can play speci®c roles in various cell types (Chen et al, , 2000Tu et al, 1998;Stoletov et al, 2001). Therefore, cell lines derived from various tissues of the Nck-knockout mice could further help our understanding of Nck function.…”
Section: Future Studiesmentioning
confidence: 99%
“…Paks have previously been shown to act downstream of basic fibroblast growth factor and integrins (18) during angiogenesis and to bind the adaptor protein, NCK, an interaction required for angiogenesis (15) and the correct formation of focal adhesions (19,20). PAK2 has also been shown to induce retraction of endothelial cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in PAK function in vitro have been shown to affect endothelial contractility, retraction, and migration (14)(15)(16)(17). PAKs are activated by the growth factors basic fibroblast growth factor and VEGF and have been implicated in angiogenesis (15,18) and formation of focal adhesions (19,20); however, there is very limited information available about the functions of PAK proteins in vivo (21).…”
mentioning
confidence: 99%